Pentingnya Audit Internal dan Implementasi Teknologi untuk Mencegah Fraud di Era Transformasi Digital - Azah Tul Muazah; Ade Sumarni; Dien Noviany Rahmatika (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Every aspect of life is now easier thanks to technology such as accounting and auditing. Accountants must be able to keep up with trends. Internal audits are used to assess a company's finances. While there are many ways to control conditions that often occur in companies, this study found that internal audits are essential to control these conditions, especially when controlling disruptions with technology. Using a literature review, this study used the results of 31 relevant journals. The results of the study show that the conditions are increasingly diverse. The solution to this problem is that companies must take action by increasing their internal oversight and supporting the advancement of information technology. Internal audits are an important part of maintenance management.